Cross-Kingdom RNAi of Pathogen Effectors Leads to Quantitative Adult Plant Resistance in Wheat - Schaefer, Luisa Katharina; Parlange, Francis; Buchmann, Gabriele; Jung, Esther; Wehrli, Andreas; Herren, Gerhard; Müller, Marion Claudia; Stehlin, Jonas; Schmid, Roman; Wicker, Thomas; Keller, Beat; Bourras, Salim (Frontiers in Plant Science, 2020)
Cross-kingdom RNAi is a biological process allowing plants to transfer small regulatory RNAs to invading pathogens to trigger the silencing of target virulence genes. Transient assays in cereal powdery mildews suggest that silencing of one or two effectors could lead to near loss of virulence, but evidence from stable RNAi lines is lacking. We established transient host-induced gene silencing (HIGS) in wheat, and demonstrate that targeting an essential housekeeping gene in the wheat powdery mildew pathogen (Blumeria graminis f. sp. tritici) results in significant reduction of virulence at an early stage of infection. We generated stable transgenic RNAi wheat lines encoding a HIGS construct simultaneously silencing three B.g. tritici effectors including SvrPm3a1/f1, a virulence factor involved in the suppression of the Pm3 powdery mildew resistance gene. We show that all targeted effectors are effectively downregulated by HIGS, resulting in reduced fungal virulence on adult wheat plants. Our findings demonstrate that stable HIGS of effector genes can lead to quantitative gain of resistance without major pleiotropic effects in wheat.